Acceleration of Wound Healing through Amorphous Calcium Carbonate, Stabilized with High-Energy Polyphosphate - Shunfeng Wang; Meik Neufurth; Hadrian Schepler; Rongwei Tan; Zhending She; Bilal Al-Nawas; Xiaohong Wang; Heinz C. Schröder; Werner E. G. Müller (Pharmaceutics, 2023)
Amorphous calcium carbonate (ACC), precipitated in the presence of inorganic polyphosphate (polyP), has shown promise as a material for bone regeneration due to its morphogenetic and metabolic energy (ATP)-delivering properties. The latter activity of the polyP-stabilized ACC (“ACC∙PP”) particles is associated with the enzymatic degradation of polyP, resulting in the transformation of ACC into crystalline polymorphs. In a novel approach, stimulated by these results, it was examined whether “ACC∙PP” also promotes the healing of skin injuries, especially chronic wounds. In in vitro experiments, “ACC∙PP” significantly stimulated the migration of endothelial cells, both in tube formation and scratch assays (by 2- to 3-fold). Support came from ex vivo experiments showing increased cell outgrowth in human skin explants. The transformation of ACC into insoluble calcite was suppressed by protein/serum being present in wound fluid. The results were confirmed in vivo in studies on normal (C57BL/6) and diabetic (db/db) mice. Topical administration of “ACC∙PP” significantly accelerated the rate of re-epithelialization, particularly in delayed healing wounds in diabetic mice (day 7: 1.5-fold; and day 13: 1.9-fold), in parallel with increased formation/maturation of granulation tissue. The results suggest that administration of “ACC∙PP” opens a new strategy to improve ATP-dependent wound healing, particularly in chronic wounds.